(untitled) - Grant, Linda (Boston, MA., 2007)
Offering a lively and communicative approach for increasing pronunciation speaking skills, Well Said Intro provides beginning to intermediate students with the pronunciation and speaking tools they need to communicate in social, academic, and professional. Increased emphasis on pair and small group activities helps students practice their pronunciation and listening skills in a contextualized setting.
Keywords: Listening,English language; Foreign speakers